"Dengarlah, Anakku dan Tinggallah Aman!": Sebuah Analisis Retorik dari Amsal 1:8-33 - Stephen Coleman (Verbum Christi: Jurnal Teologi Reformed Injili, 2023)
While Wisdom’s speech in Proverbs 1: 20-33 may or may not have been composed as an independent poem, its function within the structure of the prologue complements the initial discourse (Proverbs 1: 8-19). Wisdom picks up and furthers three main themes of the father’s instructions, specifically the notion of the divine authority of wisdom, the nature and urgency of character development, and the reality of the deed-consequence nexus. Taken together, both discourses share the same rhetorical purpose: they are designed to persuade the listening youth of the need to establish character at an early age by heeding the wisdom and instruction of his parents.